The Radiologically Equivocal Bone Lesions Finally Diagnosed by Bone Scan - Mai Amr Elahmadawy; Mahmoud Akram; Ahmed Zaher (Swiss Journal of Radiology and Nuclear Medicine)
Bone scintigraphy remains the second highest volume procedure in nuclear medicine laboratories with diverse applications. Bone scans are highly sensitive and can detect abnormalities much earlier than conventional X-rays. They provide a full-body image, allowing for the assessment of multiple bone sites simultaneously. they can also show specific patterns associated with specific diseases, eliminating ambiguity in diagnosis and establishing a specific diagnosis. Bone scan may be the final station to confirm the diagnosis of certain bone lesions that appear equivocal on other imaging modalities.  There are some conditions where bone scans can be considered accurate and guide precise diagnosis, particularly when interpreted in conjunction with clinical findings and/or  other imaging modalities as bone metastases, myositis ossificans, osteomyelitis, discitis, avascular necrosis, metabolic bone disease, fibrous dysplasia, osteopetrosis, stress fractures, Rheumatoid arthritis, reflex sympathetic dystrophy, transient migratory osteoporosis, hypertrophic osteoarthropathy, osteoid osteoma, condylar hyperplasia and osteopoikilosis.